O rio uruguai como estratégia de contextualização para ensino em uma unidade de restrição de liberdade para adolescentes - Pessano, Edward Frederico Castro; Dávila, Eliziane da Silva; Ocampo, Daniel Morin; Miralha, Cynara Terezinha Teixeira; Folmer, Vanderlei; Puntel, Robson Luiz (Góndola, enseñanza y aprendizaje de las ciencias, 2015)
Historically, teaching processes in units with freedom restriction have various problems and complexities that surpass the educational and pedagogical issues, which, in turn, make the rehabilitation process vary hard and almost inefficient. Accordingly, bet in an attractive and focused education (i.e. from the adolescents reality) can be one strategy to minimize related problems, tentatively to increase their interested in returning to school environment when released (in freedom). Thus, this study aims to evaluate the application of a pedagogical strategy based on the contextualization of teaching, by using the Rio Uruguay as a theme, in order to improve the educational process in a school located within a freedom restriction institution. The contextualization of teaching occurred associated to the methodology of continuing education of teachers, followed by interdisciplinary problematizing of the teaching. The major findings of this study highlight to the increase in the motivation of teachers to develop their work in the socio-educational institution, and also to the greater participation and academic success of students during and after the project developed, respectively. Based on this, we believe that the project/intervention could, putatively, have contributed to social and cognitive training of the students. Additionally, we believed that this intervention have contributed to make the educational environment within this educational unit less difficult and complex in their relations.